Douglas and Jones's administrative law - Douglas, Roger (Roger Neil); Jones, Melinda (Annandale, N.S.W. : Federation Press, 2002)
With well-written and considerable commentary, in addition to cases illustrating the relevant law, this book is an authoritative guide to Administrative Law in Australia. The featured cases cover a range of subjects, from land rights for Indigenous people, to commerce, the environment, social security, civil liberties and human rights.
Includes index.
Previous ed.: 1999.
Bibliography: p. 805-822.
Keywords: Administrative law -- Cases; Administrative law -- Australia -- Cases; Administrative law -- Australia